Integrating the Calculation of Preemption and Persistence Related Cache Overhead - Rashid, Syed Aftab (2016)
Work in Progress Session, IEEE Real-Time Systems Symposium (RTSS 2016). 29, Nov to 2, Dec, 2016. Porto, Portugal.